(untitled) (Polish Yearbook of International Law, 2021)
The Court of the Eurasian Economic Union was created in 2015 as a judicial organ with jurisdiction over a range of subject matters within the Eurasian Economic Union. It replaced the Court of the Eurasian Economic Community, which operated within the Eurasian Economic Community and its Customs Union (2012-2014). Though the Union become the next step in the integration process of the post-Soviet area, the newly created Court has not been given de jure a successor status. The Court of the Union was set up anew as one of the four institutional bodies in the structure of the Union. It was empowered to settle disputes between the Member States, as well as to consider different types of actions brought by private actors (economic entities only). The interpretative function of the Court was enshrined as “competence on clarification.” Moreover, the Commission, the main executive and regulative organ, was not given locus standi in actions against the Member States to enhance their compliance with the obligations of EAEU law. Preliminary jurisdiction was also cut down as compared to the Court of the Community or other regional integration courts. However, some new functions were given to the Court, and its five years long practice shows a clear tendency to substitute missing powers with those given but in a broader context, as well as its aspirations to play a consolidating role for the legal order of the Union.